Sistem Pendukung Keputusan Metode Electre pada Bauran pemasaran (7P) dalam Memulai Usaha Jasa Center - Sutrisno Sutrisno; Agus Darmawan; Fanisya Alva Mustika (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
When starting a business, many prospective entrepreneurs find the capital an obstacle because they thinkthat they do not have enough capital. In fact, to run a business, the most important capital is a non-material capital such as marketing management science with marketing mix theories. The marketing tool is known as "4P" and developed into "7P", namely: Product, Price, Place/ Distribution, Promotion, People, Physical Evidence and Process. Based on these problems, a research is conducted to design a decision support system that helps to assist prospective entrepreneurs in determining the type of business based on 7P criteria. The method used in this research is Electre (Elimination and Choice Translation Reality) method. The result of this research is a decision support system of determining the type of business based on seven criteria (7P) in determining the type of business.